Independent relationship between uveitis and increased left atrial volume index in ankylosing spondylitis patients (Annals of Medical Research, 2024)
Aim: The aim of this study was to evaluate the relationship between uveitis and left atrial volume index (LAVI) in patients with ankylosing spondylitis (AS).Materials and Methods:  Demographic, clinical, echocardiographic and brachial artery flow-mediated dilation measurement data of patients diagnosed with AS were recorded prospectively between January 2019 and June 2023. The patients were categorized into two groups: increased (group 2) and normal (group 1) based on a cut-off value of 34 ml/m2 for increased LAVI and the data were compared.Results: Of the 89 patients with AS, 54 were male and 35 were female, with a mean age of 42.8±11.8 years. There were N=67 patients in the group with normal LAVI levels, and N=22 patients in the group with high LAVI levels. Mean age, uveitis and comorbid conditions were higher in Group 2. Among the basic echocardiographic parameters that may affect LAVI, only the left ventricular mass index was different in group 2. In Group 2, flow-dependent dilatation in the vessel decreased. When we evaluated all parameters by multivariate logistic regression analysis, we found that age (odds ratio:1.097; 95% confidence interval:1.017-1.183; P=0.016) and the presence of uveitis (odds ratio:21.3; 95% confidence interval:2.476-182.1; P=0.005) independently predicted group 2.Conclusion: Evaluation of LAVI in AS patients with uveitis may be a guide in predicting the risk of cardiovascular events and early treatment.
Keywords: Ankylosing spondylitis; Left atrial volume index; Uveitis